Comparative Evaluation of the Predictive Value of Hematological Scoring System(HSS) and Acute Inflammatory Markers(Micro ESR and CRP) in Early Diagnosis of Neonatal Sepsis - Saxena, Ayush; Gupta Devra, Anshu; Kaur, Kiranjot; Pendharkar, Devyani; Sengar, Kangana (Journal of Neonatal Surgery, 2025)
INTRODUCTION: Neonatal sepsis is a major cause of morbidity and mortality in newborns globally, requiring prompt and precise diagnosis to ensure timely treatment and improve survival rates. The challenge lies in the nonspecific clinical signs and the delay in obtaining blood culture results. This study evaluates the diagnostic effectiveness of the Hematological Scoring System (HSS), rs, in comparison with acute inflammatory markers like Micro-Erythrocyte Sedimentation Rate (Micro-ESR) and C-Reactive Protein (CRP). AIM: The aim of the study was to identify the most reliable method, either standalone or in combination, for diagnosing neonatal sepsis early. METHODOLOGY: Study took into consideration 50 blood samples of suspected neonatal sepsis, which were then divided into groups(1,2,3) depending on their score and culture status. Performance analysis of hematological parameters constituting HSS, micro-ESR and CRP was calculated. RESULT: Of the 7 parameters that constituted HSS Score, maximum correlation with culture positivity was noted with Immature Neutrophil Count and Immature to Total Neutrophil Ratio (100% each) followed by Immature to Mature Neutrophil Ratio (70%).